Technology for EFL Learners: TED Talks as Technology Resources in Learning English Voice and Accent - Eka Nurhidayat; Eva Fitriani Syarifah (IJIE (Indonesian Journal of Informatics Education), 2019)
Problems that often arise in teaching English voice and Accent are limited material and references used. The integration of ICTs in EFL learning offers some tools to learn English voice and accent. One of them is TED Talks. TED Talks is a website and a downloaded application where the video is shared in which you can see a wide variety of English speakers in many parts of around the world speaking. This study aims to reveal students’ ability in analysing English Accents during the implementation of TED Talks video and the students’ response regarding the implementation of TED Talks video in learning voice and accents. In this action research, we propose a reflection on the incidence of TED talks on the teaching and learning of voice and accents. The instruments used to collect data were interviews, questionnaires, and teacher journals. The results of this study indicated that the students’ ability in analysing English voice and accents were improved. They enable to differentiate several of English accents. Moreover, they also have better understanding related to the message conveyed from the video they watched. Besides, the students gave positive responses to the implementation of TED Talks video. Most of them mentioned that TED Talks video helps them to comprehend English voice and accents better. Thus, TED talks prove to be a useful material for English teaching as a foreign language considering that they assemble many characteristics that catch students’ attention and get them related with the language spoken in actual contexts.